Cultural activities and all-cause mortality among Finnish adults: a 19-year follow-up - Tellervo Nenonen; Anne Kouvonen; Tommi Härkänen; Tuija Martelin (BMC Public Health)
Abstract Background The association between active cultural and leisure participation and lower all-cause mortality is well established. However, less is known about the specific role of different cultural activities. Baseline data from 2000, combined with mortality data up to 2019, provide a unique opportunity to examine the association between cultural activity and all-cause mortality. Methods We examined this association using data from the Finnish Health 2000 study (6,548 participants aged 30 years and older), linked to mortality follow-up data (1,789 deaths) up to the end of 2019 obtained from Statistics Finland. Cultural activity was measured as: 1) event participation (visiting cultural events or going to the theater, cinema, concerts, and art exhibitions); 2) reading and listening to music (reading books, listening to records and tapes); and 3) artistic and productive activities (singing, playing an instrument, painting, handicrafts, photography and collecting). Hazard ratios were estimated using the Cox proportional hazards models, adjusting for key sociodemographic variables, health, and health behaviors. Men and women were analyzed separately. Results For women, intermediate levels of engagement in all three domains as well as high levels of engagement in event participation and artistic and productive activities were associated with a lower risk of mortality. For men, intermediate and high levels of engagement in event participation as well as high levels of engagement in artistic and productive activities were associated with a lower risk of mortality. Conclusions The results corroborate the findings of earlier research showing that cultural activity is associated with lower all-cause mortality. However, the possibility of reversed causality or the role of unmeasured factors cannot be ruled out, even though a range of relevant confounders were controlled for. Assessing the mechanisms behind the association was beyond the scope of this study. The study suggests that engagement in cultural activities could be one factor associated with longevity, but more research is needed to examine the causality.